A Tale of Two Tests (and of Two Examinees). Issue 2 (24th May 2016) - Clauser, Amanda L.; Wainer, Howard
Abstract : It is widely accepted dogma that consequential decisions are better made with multiple measures, because using but a single one is thought more likely to be laden with biases and errors that can be better controlled with a wider source of evidence for making judgments. Unfortunately, advocates of using multiple measures too rarely provide detailed directions of exactly how to use them. In this article, we describe one source of problems with multiple measures and lay out a strategy for finding solutions.